Diagnosis of Ticks Boophilus annulatus (Say, 1821) Prying on Cows in Tikrit/Iraq - Tawfeeq, Alaa Emad; Al Tikriti, Ali Hossen Altaef (Journal for Research in Applied Sciences and Biotechnology, 2024)
The study aimed to investigate the tick insect on cows in Tikrit city for period from the beginning of November 2018 until the end of March 2019. The results of the present study showed that cows were infected with one type of tick, Boophilus annulatus (say, 1821) parasitic on cows in atrium areas and the animal chest, rate of infection was 23.076%. The diagnosis was made based on phenotypic and standard traits.